PEMBERDAYAAN PSIKOLOGI : HUBUNGANNYA DENGAN KEPUASAN KERJA DAN KOMITMEN AFEKTIF - Andreas Wahyu Gunawan; Okta Viyanita (Media Riset Bisnis & Manajemen, 2012)
The purpose of this research is to analyze the relationship between Psychological empowerment toward Job satisfaction and Affective commitment in Hasanah Graha Afiah Hospital, Depok. In this research, the researcher used descriptive statistic analysis and correlation coefficient in SPSS 11.5 software. Total sample of this research is 115 employees in this hospital. The conclution's result from this research is most of the gender that worked in Hasanah Graha Afiah Hospital is woman with total result with 82,6%, age from 24-26 years is 67,8%, and have been worked from 1-3 years is 46,1%. This research used hypotheses test toward every variable dimension through individual analysis based on any informations related to Psychological empowerment (mean score 3.89) toward Job satisfaction (mean score 3.85) and Affective commitment (mean score 3.92). Based on the relation analysis of Psychological empowerment toward Affective commitment and Job satisfaction showed that there was a significant relation between Psychological empowerment toward affective commitment and Job satisfaction with the Pearson Correlation's value for each relationship was 0.785 and 0.570.Keywords: Psychological empowerment, Affective commitment, Job satisfaction